The influence of business ethics and community outreach on faculty engagement: The mediating effect of legitimacy in higher education - Alicia Blanco-González; Cristina Del-Castillo-Feito; Giorgia Miotto (European Journal of Management and Business Economics (EJM&BE), 2021)
Purpose - The aim of this paper is to measure the effects of universities' ethical management and positive impact on society affect the faculty engagement through the mediating effect of organizational legitimacy. Design/methodology/approach - Engaged employees are characterized by better performance, increased productivity and by generating higher customer loyalty as well greater economic profit. The commitment to the organization they work for is affected by internal and external inputs. Among these, business ethics and corporate community outreach are key factors for improving employee engagement. The authors developed a survey that was distributed to professors of Spanish universities. To treat the data and test the proposed hypotheses, the authors applied structural equations through PLS-SEM. Findings - This research contributes to the organizational management field literature and advises university administrators to adopt an ethical management style based on information transparency, accountability and faculty member involvement in the decision-making process in order to improve their engagement and, therefore, increasing student satisfaction, academic results and positive impact on the common good. Originality/value - The novelty of the authors' research stands in the inclusion of legitimacy as a mediation effect between business ethics and community outreach that affect employees' engagement and, specifically, faculty engagement.
Keywords: M14; M31; 650; Community outreach; Engagement; Ethics; Higher education; Legitimacy